2016
DOI: 10.1002/2016gl069368
|View full text |Cite
|
Sign up to set email alerts
|

The permanently shadowed regions of dwarf planet Ceres

Abstract: Ceres has only a small spin axis tilt (4°), and craters near its rotational poles can experience permanent shadow and trap volatiles, as is the case on Mercury and on Earth's Moon. Topography derived from stereo imaging by the Dawn spacecraft is used to calculate direct solar irradiance that defines the extent of the permanently shadowed regions (PSRs). In the northern polar region, PSRs cover ∼1800 km2 or 0.13% of the hemisphere, and most of the PSRs are cold enough to trap water ice over geological time peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 55 publications
3
46
0
Order By: Relevance
“…Presently, Ceres's obliquity is about 4° [ Russell et al , ]. Due to this low obliquity, permanently shadowed regions have been detected on Ceres's surface using the Dawn Framing camera images and shape‐based illumination modeling [ Schorghofer et al , ; Platz et al , ]. This makes Ceres only the third body in the solar system after the Moon [ Zuber and Smith , ; Mazarico et al , ] and Mercury [ Chabot et al , ; Neumann et al , ] with identified PSRs.…”
Section: Introductionmentioning
confidence: 99%
“…Presently, Ceres's obliquity is about 4° [ Russell et al , ]. Due to this low obliquity, permanently shadowed regions have been detected on Ceres's surface using the Dawn Framing camera images and shape‐based illumination modeling [ Schorghofer et al , ; Platz et al , ]. This makes Ceres only the third body in the solar system after the Moon [ Zuber and Smith , ; Mazarico et al , ] and Mercury [ Chabot et al , ; Neumann et al , ] with identified PSRs.…”
Section: Introductionmentioning
confidence: 99%
“…Schorghofer et al (2016) have illustrated these temperatures for Ceres. At current obliquity, 4°, CO 2 , SO 2 , and NH 3 could be trapped in shallow PSRs near the rotational poles.…”
Section: Cold-trapping Of Icesmentioning
confidence: 99%
“…Table 2 shows the model results for various scenarios. The first row corresponds to an equatorial source of water molecules, within 40  , as was assumed in Section 3 and in Schorghofer et al (2016). The second row corresponds to a geographically uniform source, where a slightly higher fraction is captured, because launch velocities are lower at the more polar latitudes and the source is on average closer to the cold traps.…”
Section: Cold-trapping Of Icesmentioning
confidence: 99%
See 1 more Smart Citation
“…This is difficult to reconcile with the SEP hypothesis (Villarreal et al, ) as a sole source of the exosphere, as an SEP event would cause an isolated spike in vapor rather than continuous production necessary to maintain an exosphere in the time between the successive detections reported by Küppers et al (). Ultimately, most of the vapor around Ceres will be lost to space and a very small amount will end up in the persistently shadowed regions at the poles (e.g., Schörghofer et al, ).…”
Section: Introductionmentioning
confidence: 99%